Health-related quality of life of patients with idiopathic pulmonary fibrosis: a systematic review and meta-analysis - Ingrid A. Cox; Nicolas Borchers Arriagada; Barbara de Graaff; Tamera J. Corte; Ian Glaspole; Stella Lartey; E. Haydn Walters; Andrew J. Palmer (European Respiratory Review, 2020)
Idiopathic pulmonary fibrosis (IPF) is one of the most common forms of interstitial lung disease presenting in persons 50 years and older. Through a comprehensive review of available studies, we aimed to assess health-related quality of life (HRQoL) of people living with IPF and the instruments used in this assessment. Searches were conducted up to May, 2020. Quality appraisal and data extraction were performed using pre-designed forms. Narrative synthesis approach was used to report results of the systematic review and a random effects model was used for the meta-analysis. A leave-one-out sensitivity analysis was performed, and a trim and fill method was used to assess publication bias. The review included 134 studies. The most used instruments to measure HRQoL were St George's Respiratory Questionnaire (SGRQ), Short Form 36 (SF36) and EuroQoL (EQ5D). Standardised mean scores (95% confidence interval) for these instruments were as follows: SGRQ total score: 44.72 (42.21–47.22); SF36 physical component score (PCS): 37.00 (34.74–39.26) SF36 mental component score (MCS): 50.18 (48.41–51.95); King's Brief Interstitial Lung Disease questionnaire total score: 58.38 (55.26–61.51); and EQ5D utility: 0.73 (0.68–0.79). Analysis of standardised means for both SGRQ and SF36 demonstrated worse scores in physical health domains as compared to mental health domains. This systematic review confirms that IPF negatively affected HRQoL, mostly impacting the physical health domains. This study also demonstrated that a diverse number of instruments are used to evaluate HRQoL. In view of this diversity, a standardised approach to measurement of HRQoL for IPF is important to ensure that comparisons made are reliable.